SOURCES OF ENGLISH IDIOMS - Ruziboyev Quvonchbek Ergash o’g’li; Begizova Madina Karimovna (Zeta Repository, 2023)
The article is devoted to the study of etymology of English idioms. As a result of analysis of phraseological dictionaries, the following sources of their formation were identified: historical facts, traditions, legends, literary quotations, professional expressions, shortening of proverbs to a certain part, borrowings and many other ways.